Peran Guru Musyrif Asrama Dalam Penguatan Hafalan Santri Program Tahfidzul Qur’an - Putra, Ary Antony; Sholeh, Ahmad; Jannah, Miftahul; Muliadi, Muliadi (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2025)
Madrasatul Qur'an Islamic Boarding School is an Islamic boarding school that has a tahfidzul qur'an program. Students who memorize the Qur'an thoroughly are the priority of the Ustadz/Ustadzah/Boarding Teacher (musyrif) in guiding students for 24 hours. The purpose of this study was to determine the role of the Boarding Teacher in strengthening students' memorization. Data collection was carried out using interview and documentation techniques by asking research questions to the boarding teacher about his role in strengthening students' memorization, after the data was collected, data analysis was carried out using qualitative descriptive techniques. The results of the study showed that the role of the musyrif teacher in strengthening memorization can be seen from the aspects of murojaah, mentoring and coaching, the use of various tahfidzul qur'an learning methods, providing memorization targets to students, providing services and guidance to students who have difficulty following the tahfidzul qur'an program. Based on the results of the study, it can be concluded that the strength or weakness of students' memorization is determined by the role of the dormitory teacher (musyrif) in achieving the students' memorization targets so that the students can obtain a lot of memorization and mutqin.